Development of a low cost precision blood resistivity measurement device based on Thompson Lampard theorem - Anas, Mohd Noor; Ahmad Nasrul, Norali; Mahfoozur, Rehman, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/